Experiences of nurses involved in air ambulance service: A qualitative study - Wang, Kuei-Ying; Hu, Fang-Wen; Yu, Shu-Chen; Lin, Yohana Yobelina; Han, Chien-Ying (Universitas Airlangga, 2024)
Introduction: Nurses undertaking air ambulance service encounter environmental, equipment, and personnel limitations during their work. Moreover, they must cope with various types of injuries and illnesses, as well as changes in patient conditions. These factors pose a significant pressure on nurses. Currently, there is a lack of qualitative research on the experiences of nurses performing air ambulance tasks. The purpose of this study is to explore the experiences of nurses undertaking air ambulance service, with a focus on capturing their personal perceptions regarding this field of work. Methods: Twelve nurses were selected using purposive sampling, and semi-structured interviews were conducted to collect data. Content analysis was used to analyze the data. Results: The analysis identified three major themes: